2011
DOI: 10.19030/jabr.v27i6.6470
|View full text |Cite
|
Sign up to set email alerts
|

Small Business Entrepreneurships In The United States

Abstract: A small business entrepreneur is defined as an individual who establishes and manages a business for the principal purpose of profit and growth. Small businesses constitute an increasingly large proportion of businesses generally in the United States economy. They account for 39 per cent of the United States gross national product and create two out of every three new jobs in our economy. Seven important prerequisites are identified as being necessary for successfully operating a small business. These include … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…This offers an alternative to traditional funding opportunities for innovative entrepreneurs that find it difficult to raise finances via traditional methods (Ordanini, Miceli, Pizzetti, & Parasuraman, 2011). Previous studies have suggested that small firms are less likely to receive funding, and as a result, more likely to fail (Cressy, 2012: 262;Yallapragada & Bhuiyan, 2011). This study challenges the long-standing view that small firms are constrained by the amount of internal finance (Butters & Lintner, 1945;Carpenter & Petersen, 2002).…”
Section: Research Fields and The Nature Of Crowdfundingmentioning
confidence: 73%
“…This offers an alternative to traditional funding opportunities for innovative entrepreneurs that find it difficult to raise finances via traditional methods (Ordanini, Miceli, Pizzetti, & Parasuraman, 2011). Previous studies have suggested that small firms are less likely to receive funding, and as a result, more likely to fail (Cressy, 2012: 262;Yallapragada & Bhuiyan, 2011). This study challenges the long-standing view that small firms are constrained by the amount of internal finance (Butters & Lintner, 1945;Carpenter & Petersen, 2002).…”
Section: Research Fields and The Nature Of Crowdfundingmentioning
confidence: 73%
“…Small businesses account for a relatively large segment of the U.S. economy (Stewart, 2002;Kowalewski & Phillips, 2012;Yallapragada & Bhuiyan, 2011). The number of businesses that are being generated annually can present an understanding of the high percentage of small businesses and their importance.…”
Section: Small Businesses In the United Statesmentioning
confidence: 99%
“…Similarly, Mone and London (2009) argued setting meaningful and effective goals, building a climate of trust, providing constructive feedback, and recognizing employees' performance are employee engagement exercises that can lead to improved performance and business success. For small businesses to remain successful, it is imperative for the small business firm to be aware of the necessary skills and to hire employees to compensate for the missing skills (Yallapragada & Bhuiyan, 2011). Small businesses are operating in a competitive environment, which entails continuous improvements.…”
Section: Small Businesses In the United Statesmentioning
confidence: 99%
“…Business leaders and entrepreneurs need to possess a level of technological awareness that allows them to identify new technologies that will transform and shape their business models to do new things, or do things differently and to develop new products and services. One of the qualities the online businesses need to have is social media analytical skills [23]. The growth of online business makes access to knowledge virtually ubiquitous and develops social media analytical skills.…”
Section: The Qualities Of Online Businessesmentioning
confidence: 99%